Successful expansion of community‐based drug‐resistant TB care in rural Eswatini – a retrospective cohort study. Issue 10 (27th August 2019) - Kerschberger, Bernhard; Telnov, Alex; Yano, Nanako; Cox, Helen; Zabsonre, Inoussa; Kabore, Serge Mathurin; Vambe, Debrah; Ngwenya, Siphiwe; Rusch, Barbara; Tombo, Marie Luce; Ciglenecki, Iza
Abstract: Objectives: Provision of drug‐resistant tuberculosis (DR‐TB) treatment is scarce in resource‐limited settings. We assessed the feasibility of ambulatory DR‐TB care for treatment expansion in rural Eswatini. Methods: Retrospective patient‐level data were used to evaluate ambulatory DR‐TB treatment provision in rural Shiselweni (Eswatini), from 2008 to 2016. DR‐TB care was either clinic‐based led by nurses or community‐based at the patient's home with involvement of community treatment supporters for provision of treatment to patients with difficulties in accessing facilities. We describe programmatic outcomes and used multivariate flexible parametric survival models to assess time to adverse outcomes. Both care models were costed in supplementary analyses. Results: Of 698 patients initiated on DR‐TB treatment, 57% were women and 84% were HIV‐positive. Treatment initiations increased from 27 in 2008 to 127 in 2011 and decreased thereafter to 51 in 2016. Proportionally, community‐based care increased from 19% in 2009 to 77% in 2016. Treatment success was higher for community‐based care (79%) than clinic‐based care (68%, P  = 0.002). After adjustment for covariate factors among adults ( n  = 552), the risk of adverse outcomes (death, loss to follow‐up, treatment failure) in community‐based care was reduced by 41% (adjusted hazard ratio 0.59, 95% CI: 0.39–0.91). Findings were supported by sensitivity analyses. The care provider's per‐patient costs for community‐based (USD13 345) and clinic‐based (USD12 990) care were similar. Conclusions: Ambulatory treatment outcomes were good, and community‐based care achieved better treatment outcomes than clinic‐based care at comparable costs. Contextualised DR‐TB care programmes are feasible and can support treatment expansion in rural settings. Abstract : Objectifs: La fourniture de traitement de la tuberculose résistante aux médicaments (TB‐R) est rare dans les pays à ressources limitées. Nous avons évalué la faisabilité des soins ambulatoires de la TB‐R pour l'extension du traitement en zone rurale d'Eswatini. Méthodes: Des données rétrospectives au niveau du patient ont été utilisées pour évaluer la fourniture d'un traitement ambulatoire de la TB‐R dans la zone rurale de Shiselweni (Eswatini), de 2008 à 2016. Les soins pour la TB‐R étaient dispensés soit en clinique sous la direction d'infirmiers ou en milieu communautaire au domicile du patient avec l'implication des aidants au traitement pour la fourniture d'un traitement aux patients ayant des difficultés à accéder aux établissements. Nous décrivons ici les résultats programmatiques et avons utilisé des modèles de survie paramétriques flexibles multivariés pour évaluer le délai d'apparition de résultats défavorables. Les deux modèles de soins ont été chiffrés dans des analyses supplémentaires. Résultats: Sur 698 patients initiés sous traitement de la TB‐R, 57% étaient des femmes et 84% étaient VIH positifs. Les initiations aux traitements sont passées de 27 en 2008 à 127 en 2011 et ont ensuite diminué à 51 en 2016. Proportionnellement, les soins communautaires ont augmenté de 19% en 2009 à 77% en 2016. Le taux de réussite du traitement était supérieur pour les soins communautaires (79%) que pour ceux dispensés en clinique (68%, P = 0, 002). Après ajustement pour les facteurs de covariable chez les adultes ( n = 552), le risque de résultats indésirables (décès, perte au suivi, échec du traitement) dans les soins communautaires a été réduit de 41% (rapport de risque ajusté de 0, 59, IC95%: 0, 39–0, 91). Les résultats ont été étayés par des analyses de sensibilité. Les coûts par patient sur base du prestataire de soins pour les soins communautaires (13.345 USD) et en clinique (12.990 USD) étaient similaires. Conclusions: Les résultats des traitements ambulatoires ont été bons et les soins dispensés dans la communauté ont obtenu de meilleurs résultats que ceux dispensés en clinique à des coûts comparables. Des programmes de prise en charge contextualisés de la TB‐R sont réalisables et peuvent soutenir l'expansion du traitement en milieu rural.